Agenda for the third session of the 1968 Democratic National Convention (1968)
This document outlines the agenda for the third session of the 1968 Democratic National Convention held on Wednesday, August 28. The session began with formal proceedings including an invocation, presentation of colors, the national anthem sung by Mahalia Jackson, and speeches supporting both the majority and minority reports on the Vietnam platform. Numerous prominent political figures were scheduled to speak, particularly during debate over the Vietnam plank. The program also included memorials and resolutions of appreciation to party leaders and officials. The session concluded with the roll call of states for presidential nominations and the ballot for selecting the Democratic nominee.